Extracellular ATP Induces Vascular Inflammation and Atherosclerosis via Purinergic Receptor Y2 in Mice. Issue 8 (August 2016) - Stachon, Peter; Geis, Serjosha; Peikert, Alexander; Heidenreich, Adrian; Michel, Nathaly Anto; Ünal, Fatih; Hoppe, Natalie; Dufner, Bianca; Schulte, Lisa; Marchini, Timoteo; Cicko, Sanja; Ayata, Korcan; et al.
Abstract : Objective—: A solid body of evidence supports a role of extracellular ATP and its P2 receptors in innate and adaptive immunity. It promotes inflammation as a danger signal in various chronic inflammatory diseases. Thus, we hypothesize contribution of extracellular ATP and its receptor P2Y2 in vascular inflammation and atherosclerosis. Approach and Results—: Extracellular ATP induced leukocyte rolling, adhesion, and migration in vivo as assessed by intravital microscopy and in sterile peritonitis. To test the role of extracellular ATP in atherosclerosis, ATP or saline as control was injected intraperitoneally 3× a week in low-density lipoprotein receptor −/− mice consuming high cholesterol diet. Atherosclerosis significantly increased after 16 weeks in ATP-treated mice (n=13; control group, 0.26 mm2; ATP group, 0.33 mm2; P =0.01). To gain into the role of ATP-receptor P2Y2 in ATP-induced leukocyte recruitment, ATP was administered systemically in P2Y2 -deficient or P2Y2 -competent mice. In P2Y2 -deficient mice, the ATP-induced leukocyte adhesion was significantly reduced as assessed by intravital microscopy. P2Y2 expression in atherosclerosis was measured by real-time polymerase chain reaction and immunohistochemistry and demonstrates an increased expression mainly caused by influx of P2Y2 -expressing macrophages. To investigate the functional role of P2Y2 in atherogenesis, P2Y2 -deficient low-density lipoprotein receptor −/− mice consumed high cholesterol diet. After 16 weeks, P2Y2 -deficient mice showed significantly reduced atherosclerotic lesions with decreased macrophages compared with P2Y2 -competent mice (n=11; aortic arch: control group, 0.25 mm 2 ; P2Y2 -deficient, 0.14 mm2; P =0.04). Mechanistically, atherosclerotic lesions from P2Y2 -deficient mice expressed less vascular cell adhesion molecule-1 and intercellular adhesion molecule-1 RNA. Conclusions—: We show that extracellular ATP induces vascular inflammation and atherosclerosis via activation of P2Y2 . Abstract : Supplemental Digital Content is available in the text.